Interactive online taekwondo training and education in the times of COVID-19 - Mihaylov, D. (Pedagogy, 2020)
The COVID-19 pandemic has affected the world in every aspect of our life. It produced a huge impact on sports and education. People have to adapt and change in order to maintain their normal activities. Education and sports training are of great importance to young people. In this study, I research the possibilities for trainings under COVID-19 pandemic and local lockdowns. There are several ways to continue teaching and educating students in taekwondo under the social distancing rules. The research focused on discussing the way taekwondo practicing has changed during the COVID-19 pandemic and what types of taekwondo trainings beginners, advanced and elite sportsmen prefer during the local lockdown. The study was conducted through online questionnaires and interviews with coaches and taekwondo students. It shows that there was a major decrease in the number of students practicing taekwondo and it also reveals the ongoing fear of a major part of taekwondo athletes of the coronavirus.